Jerzy Bartmiński (1939 09 19 — 2022 02 07) - Rutkovska, Kristina; Pajėdienė, Jūratė (Slavistica Vilnensis, 2022)
2022 02 07 one of the most famous linguists in the world, founder of Polish cognitive ethnolinguistics, Slavist, semanticist, axiologist and textologist Jerzy Bartmińskis, author of 12 books and more than 900 articles, editor-in-chief of the journal "Etnolingwistyka", author of the dictionary Słownik stereotypów i symboli ludowych, editor of the axiological dictionary Leksykon aksjologiczny Słowian i ich sąsiadów. He actively collaborated with Lithuanian scientists who use the methods proposed by him to study the linguistic picture of the world.
Keywords: Jerzy Bartmiński; cognitive ethnolinguistics; linguistic view of the world